2021
DOI: 10.3390/cancers13143406
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Analyses of French Canadians of Quebec Facilitate the Characterization of New Cancer Predisposing Genes Implicated in Hereditary Breast and/or Ovarian Cancer Syndrome Families

Abstract: The French Canadian population of the province of Quebec has been recognized for its contribution to research in medical genetics, especially in defining the role of heritable pathogenic variants in cancer predisposing genes. Multiple carriers of a limited number of pathogenic variants in BRCA1 and BRCA2, the major risk genes for hereditary breast and/or ovarian cancer syndrome families, have been identified in French Canadians, which is in stark contrast to the array of over 2000 different pathogenic variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 165 publications
(273 reference statements)
1
37
0
Order By: Relevance
“…Several studies on linkage analysis in non BRCA1/2 families have been conducted in other populations [ 20 25 ]. However, the fact that these findings do not replicate in other populations is not surprising given the uniqueness of this Sri Lankan data set.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Several studies on linkage analysis in non BRCA1/2 families have been conducted in other populations [ 20 25 ]. However, the fact that these findings do not replicate in other populations is not surprising given the uniqueness of this Sri Lankan data set.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…We have proposed a strategy for identifying candidate variants in new cancer predisposing genes that involves the investigation of cancer families from populations exhibiting genetic drift ( 33 ). Over time, rare PVs in such populations could attain disproportionally high carrier frequencies of rare risk variants relative to the general population ( 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our research of French Canadians (FC) from the Quebec population of Canada, identified RECQL ( 37 ) and FANCI ( 24 ) as new candidate BC or OC predisposing genes, respectively. Genetic drift in the FCs of Quebec has been attributed to common ancestors as a result of the geographic isolation and multiple waves of expansion of European settlers from France since 1608 ( 33 35 , 38 , 39 ). Investigating these populations facilitates the characterization of deleterious variants in known or candidate cancer predisposing genes as all types of variants could be investigated and not only LoF variants ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this risk increases up to 15%-45% for germline BRCA1 pathogenic variant carriers, and 10%-20% for BRCA2 pathogenic variant carriers (6). Among all hereditary OC patients, 15%-35% of pathogenic variations may be present in other tumor suppressor genes or oncogenes including mismatch repair (MMR) genes, TP53, ATM, CHEK2, PALB2, RAD50, and BRIP1 (5,7). Identifying the underlying molecular defects in ovarian cancer is an important approach for the medical management of patients and guidance regarding treatment options, and this study aimed to reveal the relationship between genetic variations and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%